Human development in the villages of Kerala: an analysis from Census 2011. Issue 6 (18th August 2022) - Das, Arijit; Das, Ketan; Basu, Tirthankar
ABSTRACT: India ranks over 100 in the Human Development Index (HDI). However, Kerala, a small coastal state of south India, has a high HDI and is commonly referred to as the master of social development. This paper analyses the nature of human development in the villages of Kerala to reveal the spatial pattern of human development at the local level. HDI is calculated following the approach of UNDP. The outcome shows that 28.75% of the villages of Kerala still need more attention to human development. Hence, this study reveals that there are some loopholes in Kerala, which need special focus.